Expert by Experience Involvement in Mental Health Nursing Education: Nursing Students' Perspectives on Potential Improvements. (2nd December 2019) - Happell, Brenda; Waks, Shifra; Horgan, Aine; Greaney, Sonya; Bocking, Julia; Manning, Fionnuala; Goodwin, John; Scholz, Brett; Jan van der Vaart, Kornelis; Allon, Jerry; Hals, Elisabeth; Granerud, Arild; et al.
Abstract: Expert by experience involvement in mental health education for health professional programmes has increased in recent decades. The related literature has articulated the benefits, and changes in attitudes have been measured in some studies. Less attention has been devoted to ways this learning approach could be improved. The aim of this paper is to present the nursing students perspectives on how Expert by Experience input into nursing curricula could be enhanced. Qualitative exploratory research was undertaken, involving focus groups with students who had completed a mental health learning module co-produced by Experts by Experience and nurse academics. Results show two main themes: getting the structure right, and changes to content and approach. Some student responses could directly influence changes to the learning module. In other instances, responses indicate the need to better prepare students of the value of lived experience knowledge in its own right, rather than adjunct to more traditional methods of education. These findings are important in encouraging reflection on how future learning modules co-produced by Experts by Experience and Mental Health Nursing academics can be refined and better articulated.